Strengthening teachers in disadvantaged schools: Evidence from an intervention in Sweden's poorest city districts - Caroline King Barnard Hall; Martin Lundin; Kristina Sibbmark (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
Children growing up in disadvantaged neighborhoods tend to perform significantly worse in school compared to children growing up under more favorable circumstances. We examine the impact of a three-year program ("Coaching for Teaching") targeted at ten poorly performing lower secondary schools in Sweden's most disadvantaged city districts. The aim of the intervention was to strengthen the teachers' professional development, e.g. through coaching and further training, and thereby enhance student performance. We use a difference-in-differences design and rich register data to estimate effects on several educational outcomes. Our results show a large and statistically significant positive impact on student performance on standardized tests in English language. Estimates for test results in math are also positive and large, but not statistically significant; the same applies to GPA and admission to upper secondary school. For test scores in Swedish language there is no indication of improvement. An analysis of a survey of pupils supports the idea that the teaching as well as the classroom climate improved due to the intervention. Taken together, the program seems to have generated rather promising results in the short run.
Keywords: I20; I21; I24; I28; J24; 330; Education; disadvantaged schools; lower secondary school; social back-ground; teachers; professional development; student performance; government policy